PEMANFAATAN MEDIA AUDIO VISUAL PADA MATERI MEMANDIKAN JENAZAH DI SEKOLAH - Mulia Mulia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Research on the use of audio-visual media in schools is done because in schools there are teachers who do not use practice-based learning media even though the material is practicum. Audiovisual media students can see and hear directly the material that will be taught by the teacher. The development phase uses a 4D development model consisting of the stages of defining, designing, developing, and distributing. Audio visual-based learning media have fulfilled the validity criteria by obtaining an average score from all aspects of the validator's assessment, which is 3.65 which is in the very valid category after being revised twice, so it is feasible to use it based on expert judgment. Audio visual-based learning media has fulfilled the practical category because more than 80% of students give a positive response. The teacher's observation sheet also shows positive results.